2014
DOI: 10.3855/jidc.4292
|View full text |Cite
|
Sign up to set email alerts
|

ESBL-producing Escherichia coli and Klebsiella pneumoniae at a tertiary care hospital in Saudi Arabia

Abstract: Introduction: The increasing frequency and antibiotic resistance among extended-spectrum β-lactamases (ESBLs)-producing bacteria are posing a serious threat. This study sought to investigate the frequency and antibiotic susceptibility of ESBL-producing E. coli and K. pneumoniae at a tertiary care hospital. Methodology: Data were collected from samples sent to the microbiology laboratory between 2006 and 2010 at King Khalid University Hospital, Riyadh. ESBLs were confirmed using Etest strips of cefotaxime/cefot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 27 publications
10
22
0
Order By: Relevance
“…In this study, E. coli were highly resistant to amoxicillin 269 (73.7%) and least resistant to imipenem 7 (1.9%). This is similar to reports of different studies [21, 23, 24, 29-31, 33, 35-41]. Likewise, most Klebsiella spp.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, E. coli were highly resistant to amoxicillin 269 (73.7%) and least resistant to imipenem 7 (1.9%). This is similar to reports of different studies [21, 23, 24, 29-31, 33, 35-41]. Likewise, most Klebsiella spp.…”
Section: Discussionsupporting
confidence: 91%
“…were highly resistant to amoxicillin 18 (90%) and least resistant to gentamycin 0 (0%) and imipenem 0 (0%). Similar result was shown in different studies [29, 33, 35, 36, 38, 41, 42]. Imipenem was the most effective drug, however, it should not be administered as empirical drug unless infection is life threatening, as carbapenems are considered the drug of last resort.…”
Section: Discussionsupporting
confidence: 85%
“…Including data from our prior analysis, 11 our data demonstrate that the epidemiology of ESBL-KP remained largely unchanged from 2005 to 2014. Although the rate of ESBL-KP infections has increased in some geographic locations, 16,17 other investigators have also described a trend of stable ESBL-KP infections and rising ESBL-EC infections similar to our findings in this study. 8,18 …”
Section: Discussionsupporting
confidence: 90%
“…Similarly, studies stated that ESBL-producing Enterobacteriaceae showed high levels of resistance to other antibiotics like cotrimoxazole and ciprofloxacin [26, 27]. Therefore, ESBL-producing strains are multi-drug resistant bacteria thus pose challenging scenario for empirical therapy of invasive infections.…”
Section: Discussionmentioning
confidence: 99%